Effect of Cinnamon (Cinnamomum burmannii) Bark Oil on Testicular Histopathology in Streptozotocin Induced Diabetic Wistar Male Rats - Mustofa Helmi Effendi (Journal of Global Pharma Technology, 2020)
The purpose of this study was to determine the effect of cinnamon bark oil (CBO) on testicular histopathology. The variables taken were the diameter of the seminiferous tubules and the number of leydig cells in the testes of white male rats (Rattus norvegicus) which had been induced by streptozotocin. Twenty white male rats adult Wistar strains aged 2-3 months with an average weight of 150-250 grams were used in this study. The rats were divided into five experimental groups (4 rats each group) treated with a combination of streptozotocin and cinnamon bark oil (CBO) which were designed as follows: K(-), K(+), P1, P2, and P3. P is white rat injected with streptozotocin with a single dose of 45 mg / kg body weight intraperitonially, followed by therapy. K(-) without streptozotocin and only given drug solvent, K(+) given drug solvent, P1 treated with CBO 100 mg / kgBB orally, P2 treated with CBO 200 mg / kgBB orally, P3 treated orally with CBO 400 mg / kg orally for 14 days. White rat animals were then mutilated and testicular organs were taken for histopathological preparations using HE staining, then the diameter of the seminiferous tubules and the number of Leydig cells were calculated. Data were analyzed with One Way ANOVA and followed by Duncan's test. The results showed that streptozotocin had the potential to reduce the size of the seminiferous tubule diameter and the number of Leydig cells, while CBO at a dose of 400 mg / kgBW could increase the size of the seminiferous tubule diameter and the number of Leydig cells. It can be concluded that CBO can be used to reduce testicular dysfunction induced in diabetic rats.Key words: Cinnamon bark oil, Seminiferous tubule diameter, Leydig cells, Streptozotocin, Male rat.